Clinical and prognostic significance of the inflammatory markers GlycA and GlycB in chronic heart failure of both ischemic and non-ischemic etiologies. (14th October 2021) - Cediel Calderon, G; Teis, A; Codina, P; Domingo, M; Santiago-Vacas, E; Spitaleri, G; Zamora, E; Santasmases, J; Alonso, N; Lupon, J; Bayes-Genis, A
Abstract: Background: N-acetylglucosamine/galactosamine (GlycA) and sialic acid (GlycB) constitute evolving nuclear magnetic resonance (NMR) biomarkers of systemic inflammation. They have been increasingly studied and associated with cardiovascular (CV) disease and incident heart failure (HF), but little is known about its value in chronic HF population. Purpose: We aimed to examine the association on long-term CV outcomes of GlycA and GlycB in chronic HF relative to aetiology. Methods: We prospectively included a cohort of 429 HF patients admitted to an ambulatory HF Unit. Plasma GlycA and GlycB concentrations were determined using NMR spectroscopy. The primary endpoint was a composite of CV death and readmission due to HF. Competing risk regression models were performed with non-CV death as the competing event. Because an interaction existed between GlycA and GlycB with ischemic etiology (p<0.01), we examined this further. Results: The mean (SD) follow-up was 4.5±2.9 years. Median concentrations (IQR) for GlycA and GlycB were 5.4 (4.9–6.2) mmol/L and 1.9 (1.7–2.2) mmol/L, respectively. A total of 92 (41.1%) and 123 (60.0%) patients from non-ischemic and ischemic etiology, respectively, the clinical endpoint. In ischaemic HF patients (47.8%; n=205) both markers were not associated with the primary endpoint. Conversely, in non-ischemic HF patients (52.2%; n=224), GlycA and GlycB exhibited association with the primary endpoint in univariable and after multivariable adjustment (HR 1.14; 95% confidence interval [CI]: 1.02–1.28, p=0.018 and HR 1.91; 95% CI: 1.27–2.88, p=0.002; respectively. Figure 1 and 2). In this subgroup, a correlation analysis with well-known biomarkers (NT-proBNP, hs-TnT and ST2) only evidenced a positively and significantly correlation of GlycB with ST2 (r=0.26, p<0.001). No association was found with NYHA functional class. Conclusions: GlycA and GlycB represent an evolving approach of inflammation status with prognostic value of long-term CV related events in non-ischemic HF patients. Funding Acknowledgement: Type of funding sources: None.